2012
DOI: 10.1016/j.neurobiolaging.2010.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in the Bengalese finch song motor program

Abstract: It is well established that there are remarkable similarities between song learning in oscine birds and acquisition of speech in young children. Human speech shows marked changes with senescence, but few studies have evaluated how song changes with advanced age in songbirds. To investigate the effect of old age on song, we compared song of old Bengalese finches (Lonchura striata domestica) with that of middle-aged birds. The main observed difference was a decrease in the song tempo, largely due to an increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 16 publications
1
29
1
Order By: Relevance
“…Such a process of motor consolidation has been previously suggested for zebra finch song based on other data (Brainard and Doupe 2001). Interestingly, one recent study has indicated opposite changes in Bengalese finch song timing in the later years of life, i.e., that songs slow down, mostly due to increases in gap duration (Cooper et al 2012).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Such a process of motor consolidation has been previously suggested for zebra finch song based on other data (Brainard and Doupe 2001). Interestingly, one recent study has indicated opposite changes in Bengalese finch song timing in the later years of life, i.e., that songs slow down, mostly due to increases in gap duration (Cooper et al 2012).…”
Section: Discussionmentioning
confidence: 61%
“…If true, the chaining hypothesis could also have one of several implications for changes to song in older Bengalese finch birds (Cooper et al 2012): the slowing of tempo could reflect a gradual weakening of synapses, although this would also imply a similar correlation between increases in gap duration and weakening of associated transition probabilities. That study did find decreases in syllable repetition rate, although a specific correlation with gap duration was not reported for those transitions.…”
Section: Discussionmentioning
confidence: 99%
“…Cardoso et al (2012) likewise found no associations between components of trill performance and condition in dark-eyed juncos ( Junco hymenalis ). A direct effect of health and condition on song performance parameters has only been described in a few species (Pasch et al 2011; Ritschard and Brumm 2012), but senescence is associated with decreased song performance in two avian species (Rivera-Gutierrez et al 2012; Cooper et al 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Increased song variability was previously observed to be correlated to the amount of song in younger adult zebra finches [N=18 between 120 and 200days old (Hilliard et al, 2012)]. Both Bengalese and zebra finches undergo age-related changes in vocal quality and the ability to exhibit vocal plasticity (Brainard and Doupe, 2001;Cooper et al, 2012), thus they may undergo age-related changes in how molecular microcircuits impact behavior. Further, age-and speciesrelated differences in basal vocal variability may have statistically limited our ability to detect these changes.…”
Section: Vocal Variability After Vocal Practicementioning
confidence: 98%